Recent developments in alternative finance empirical assessments and economic implications - Barnett, William A.; Jawadi, Fredj (Emerald, 2012)
Since the global financial crisis began in 2008-2009, there has been a strong decline in financial markets and investment, and significant economic recession for most developed and emerging economies. Accordingly, new forms of alternative finance, management, control, accounting, trading and investment are being sought. Alternative finance presents challenges intended to stimulate investment and promote economic growth and development, as well as provide a return on investment during turbulent times. This volume aims to provide the reader with a comprehensive understanding of alternative finance in its various forms. It addresses the impact of the financial crisis and the failure of monetary and financial institutions to manage financial markets and handle the recent downturn. It also presents and discusses new research findings associated with alternative forms of investment and finance, and their economic and political implications.
Keywords: Economics.; Econometrics.; elektronické knihy; electronic books